Quality of maternal and neonatal care in Central Asia and Europe—lessons learnt. (September 2014) - Bacci, A
Abstract : In the World Health Organization (WHO) European region despite official high coverage of essential interventions for maternal and neonatal care, there are still significant gaps in the delivery of effective interventions. Since 2001, WHO designed and implemented the Making Pregnancy Safer programme, which includes hands‐on training courses in effective perinatal care for maternity teams, development of clinical guidelines, maternal mortality and morbidity case reviews, and assessments of quality of care. This has contributed to enhancing capacity at country level to improve organisation and provision of care. This paper describes the programme's components, challenges, achievements and results.